The Influence of Marketing Mix, Brand Image and Knowledge on The Decision to Become a Customer at Bank Syariah Indonesia - Shelfy Ananda Rahmatika; Zanwar Ismail (Yayasan Az Zukhruf Cendikia, 2025)
Purpose – This research aims to analyze and identify the influence of the marketing mix, brand image, and knowledge on the decision to become a customer. Design/methodology/approach – This research employs a quantitative approach, using primary data collected from a population of 52 customers of Bank Syariah Indonesia. The data analysis is conducted using Partial Least Square (PLS) with Moderated Regression Analysis. Findings - This study has the results that the marketing mix has an insignificant effect on the decision to become a customer and brand image has a significant effect on the decision to become a customer, then knowledge has a significant effect on the decision to become a customer. Resarch limitations/implications – This are several limitations in this study that shoud be considered when presenting the findings. First, the respondent were obtained through Whatsapp and Instagram, so the questionnaires were not guided in detail during completion. This may lead to potential subjectivity in the respondents’ answers and delays in receiving confirmation from respondents. These factors could limit the generalizability of the study’s results. Second, time constraints and limited access to respondents resulted in a sample size that did not meet the initially planned target. Third, this study only considered three main variables—marketing mix,brand image, and knowledge—leeaving other potential factors that may influence the decision to become a customer, such as customer satisfaction, religiosity, or financial literacy, unanalyzed in depth.